2000
DOI: 10.1097/00004714-200004000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Extension of a Pilot Study: Impact From the Cytochrome P450 2D6 Polymorphism on Outcome and Costs Associated With Severe Mental Illness

Abstract: The influence of cytochrome P450 2D6 (CYP2D6) genetic variability was examined in psychiatric inpatients by evaluating adverse drug events (ADEs), hospital stays, and total costs over a 1-year period in an extension of a previously published brief report. One hundred consecutive psychiatric patients from Eastern State Hospital in Lexington, Kentucky, were genotyped for CYP2D6 expression. ADEs were evaluated by a neurologic rating scale, modified Udvalg for Kliniske Undersogelser Side Effect Rating Scale, or ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
97
1
4

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 196 publications
(105 citation statements)
references
References 23 publications
3
97
1
4
Order By: Relevance
“…Multiple prescription and over-the-counter drug use is particularly common in the U.S., a country in which genotype incidence rates are not intuitively obvious and in which a high rate of serious and fatal adverse drug reactions occurs [70]. Furthermore, a study conducted in a psychiatric setting in the U.S. has shown that CYP2D6 polymorphisms can have a marked effect on the cost of treating a patient; UM and PM patients were found to cost between $4,000 and $6,000 per year more to treat than EM or IM individuals [71]. Thus, genotyping for individuals receiving single or multiple drugs that are metabolized by CYP2D6 may help clinicians to avoid adverse drug-drug interactions and to individualize treatment with medications better.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple prescription and over-the-counter drug use is particularly common in the U.S., a country in which genotype incidence rates are not intuitively obvious and in which a high rate of serious and fatal adverse drug reactions occurs [70]. Furthermore, a study conducted in a psychiatric setting in the U.S. has shown that CYP2D6 polymorphisms can have a marked effect on the cost of treating a patient; UM and PM patients were found to cost between $4,000 and $6,000 per year more to treat than EM or IM individuals [71]. Thus, genotyping for individuals receiving single or multiple drugs that are metabolized by CYP2D6 may help clinicians to avoid adverse drug-drug interactions and to individualize treatment with medications better.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 100 consecutive psychiatric inpatients genotyped for CYP2D6 on admission, the number of adverse effects in patients treated with CYP2D6 substrates were highest in PMs and higher in IMs than in EMs or UMs. 46 The costs of treating patients of the UM or PM phenotype were found to be 4000-6000 USD higher per year than those of the IM or EM phenotype and the duration of treatment was longer among PMs. 46 With respect to treatment of schizophrenia with perphenazine, thioridazine or haloperidol, significant oversedation has been found to be linked to the CYP2D6 genotype in three different studies.…”
mentioning
confidence: 93%
“…After Affymetrix marketed the first GeneChip for HIV genotyping, it developed one for CYP2D6 and CYP2C19 testing, which appeared to be costeffective in a 1996 pilot study when first-generation psychiatric drugs were used. [16] Roche Diagnostics (Indianapolis, IN, USA) took over the marketing. [14] Some small companies developed other parallel systems of genetic testing and US labs started offering CYP2D6 and CYP2C19 testing.…”
Section: Clarifying the Fda's Rolementioning
confidence: 99%